Automatic dustbin / Mohd Addha Sha’ary Daud, Nik Afif Mustapha and Muhamad Roslaini Redzuan - Daud, Mohd Addha Sha’ary; Mustapha, Nik Afif; Redzuan, Muhamad Roslaini (2014)
The project is designed as a system that can help reduce the burden on us and helped manage the clean house or our vicinity. This project has two sensors that detect an individual that is close to the trash can and the lid opens by itself, to give opportunities for individuals to throw trash into the bins. Next, another sensor will sound when the lid which are not able to touch the surface of the buzzer. This system will bring awareness to consumers that the trash is full and also the opportunity thrown away. A key component of this project is the infrared sensor and the motor solenoid. Simulation has been exhibited through PROTHEUS as confirmation to the development of the project.